Prevalence of Psychoactive Substance Consumption in People With Obesity. (14th October 2016) - Donnadieu-Rigole, Hélène; Olive, Laetitia; Nalpas, Bertrand; Duny, Yohan; Nocca, David; Perney, Pascal
ABSTRACT: Objective : The aim of this study was to evaluate the prevalence and the kind of psychoactive substances consumed by people with obesity. Methods : Patients were included at their first visit for bariatric surgery. Socio-demographic characteristics, anxiety, depressive disorders and psychoactive substance consumption were assessed. The prevalence of psychoactive substance consumption was compared to that of the general population reported by the French National Institute of Prevention and Health Education. Results : One hundred (100) patients were consecutively recruited: 60 women (mean age 41 ± 14 years) and 40 men (mean age 46 ± 13 years). Sixty-seven percent of subjects consumed alcohol. Consumption rates of cannabis (21% vs . 10%), cocaine (7.0% vs . 0.8%) and amphetamine (6.0% vs . 0.3%) were significantly ( p < .0001) higher in people with obesity than in the general population. Conclusions : People with obesity have an excess risk of amphetamine, cocaine and cannabis consumption. This consumption may increase the risk of cardiovascular and psychiatric morbidity and should therefore be detected before surgery.